(untitled) (Jahangirnagar University Journal of Biological Sciences, 2020)
Four commercial root samples (CS1, CS2, CS3 and CS4) of Hemidesmus indicus alongside an authentic sample (HI) were evaluated following antibacterial potential, cytototoxicity and DPPH free radical scavenging activity assay. The inhibition zones produced by commercial samples ranged between 9.5 to 13.5 mm against the tested bacteria in antibacterial sensitivity test. HI produced highest inhibition zone recorded as 20.63 mm against Staphylococcus aureus followed by 17.4 mm against Bacillus subtilis at 150 μg/ml concentration. HI also showed highest cytotoxicity with LC50 value of 1.726 mg/ml, 4.754 mg/ml and 13.247 mg/ml after 6 hours, 12 hours and 24 hours respectively in brine shrimp lethality assay. Sample CS1 and CS2 showed less cytotoxicity compared to CS3 and CS4. Depending on the concentration of extracts, the DPPH free radical scavenging activities of commercial samples were in close proximity with HI. The total phenolic content in HI was 54.52 mg/ml while in four commercial sample, it ranged between 52.28 to 75.37 mg/ml gallic acid equivalent (GAE) per 100 mg extract. Jahangirnagar University J. Biol. Sci. 8(2): 61-69, 2019 (December)